INTERNALISASI NILAI-NILAI PANCASILA PADA SISWA SD KELAS 4 DI SEKOLAH INDONESIA MAKKAH - Siti Rahmawati; Tri Joko Raharjo; Harianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The love for one's country is increasingly being degraded among young people in the contemporary era due to students' lack of extensive knowledge and understanding of national culture. This correlates with students' learning and sense of nationalism which is starting to disappear due to developments over time and the impact of westernization. The research conducted by researchers used a qualitative research approach design with a case study method. This research chose the Elementary School at Makkah Indonesian School for grade 4 students as the research location because the school consists of heterogeneous student conditions with data collection techniques through interviews, observation, and documentation. The data analysis techniques in this research are data reduction, data presentation, and conclusion. From the research carried out, it can be concluded that the Makkah Indonesian School already understands the description and objectives regarding Pancasila values education, the principal and teachers have planned the implementation of Pancasila values education, and the realization of Pancasila values education has been seen. implemented optimally, and in the evaluation of Pancasila values education at the Makkah Indonesian School, there are still at least not very significant obstacles Keywords: Pancasila, Education, Mecca Indonesian School